Irony According to Rorty’s Human Philosophy Perspective - Martina Prativi; Ahsan Siraj (Humaniora, 2021)
In the humanist philosophy of Richard Rorty, the existence and concept of nihilism is used to scrutinize the theory of irony. Nihilism and the humanitarian crisis of cruelty underpin Rorty’s philosophical thinking. One of his basic ideas is how humans have a particular attitude in perceiving reality, which can be found in terms of irony. This term provides a humanist grounding for coping with humanitarian issues in the present day, in this regard functioning as a frame for understanding put forward by Rorty within human selfhood. This literature review is based on both primary and secondary sources, with the formers referring to books written by Rorty, while the latter comprises information from books, journals, articles, and research papers discussing Rorty and human philosophy, especially existentialism. The research steps undertaken were data collection, classification, description, and analysis, and methodological elements were interpretation, heuristics, compilation, and reflection. The results provide an understanding of the use of Rorty’s word, “irony,” a consequence of humans tending to overlook their position as human beings. Humans are apparently ironic for seeing things critically, yet are capable of taking steps in any conditions. The meaning of irony can be understood as humans in the present day acting for others (in a social context). The virtue of ironists is conscious thought that may exist regarding the presence of others inside themselves, with language simply being an intermediary, functioning as a tool for dialectical needs. Humans construct history by considering three things that can be classified as morality, language, and socially constructed basic investigations.